SARS-COV-2 (COVID-19) EXAMINATION USES ANTIGEN SWAB FOR COMPANY’S EMPLOYEES IN SURABAYA ON JULY – AUGUST 2021 - Lukas Slamet Riadi; Yudhiakuari Sincihu; Mulya Dinata; Vincentius Diamantino Supit; Juanita Harrisa; Putri Lisdiyanti (JURNAL WIDYA MEDIKA, 2022)
Background of the problem: Since 2020, all the countries in the world has been rocked by Covid-19 (Sars-Cov-2) pandemic. Since July 2021, Indonesia became Covid-19 epicentrum with the highest mortality 2.048 people in the world on 10th August 2021. Covid-19 supporting diagnosis checkup uses RT-PCR and Antigen rapid test, this was based on the Indonesian Health Minister instruction about the uses of antigen test for 2019 Corona Virus Disease checkup. Method: This research uses cross sectional, retrospective analytic study by seeing the data that was taken from SARS-Cov-2 antigen rapid test from some location of companies in Surabaya. The swab data is from Sentra Medika Clinic Surabaya by using nasopharyngeal and nasal antigen SARS-CoV-2 rapid test kit (immunochromatography method). Result: The main data of labor’s characteristics is 6033 people. The highest number was on July to August 2021 on the age range of 30-39 years old (39,70%), meanwhile at the age of 60-69 years old is 0,45%. In the case of Covid-19 virus infection, the highest number of positive antigen was at the age range of 30-39 years old was 64 people (41,30%), whereas 2 people (1,30%) were at the age range of 60-69 years old. At the age more than 60, the number of case is not many but the statistic analytic result shows that age influences P0,05 (P 0,260) Covid-19 Antigen swab test result. The case spike happened on July 2021, 153 people were positive of Antigen swab test: 141 people were men (92,16%) and 12 people were women (7,84%). On August 2021, 2 men were positive (100%). Conclusion: The result of the research in July 2021 shows that the highest numbers of labor are at the age of 30-39 years old. The risk of Covid-19 infection mostly at men. Whereas Covid-19 infection risk is at the age of 60-69 years old are in small amount. Age influences the result of Covid-19 Antigen swab test. Meanwhile, gender does not influence the result of Covid-19 Antigen swab test.